Indic Manuscript Cultures through the Ages : Material, Textual, and Historical Investigations - Cuneo, Daniele; Formigatti, Camillo Alessio; Vergiani, Vincenzo (2017)
This collection of essays explores the history of the book in pre-modern South Asia looking at the production, circulation, fruition and preservation of manuscripts in different areas and across time. Edited by the team of the Cambridge-based Sanskrit Manuscripts Project and including contributions of the researchers who collaborated with it, it covers a wide range of topics related to South Asian manuscript culture: from the material dimension (palaeography, layout, decoration) and the complicated interactions of manuscripts with printing in late medieval Tibet and in modern Tamil Nadu, to reading, writing, editing and educational practices, from manuscripts as sources for the study of religious, literary and intellectual traditions, to the creation of collections in medieval India and Cambodia (one major centre of the so-called Sanskrit cosmopolis), and the formation of the Cambridge collections in the colonial period. The contributions reflect the variety of idioms, literary genres, religious movements, and social actors (intellectuals, scribes, patrons) of ancient South Asia, as well as the variety of approaches, interests and specialisms of the authors, and their impassionate engagement with manuscripts.